Technical Aspects and Clinical Limitations of Sperm DNA Fragmentation Testing in Male Infertility: A Global Survey, Current Guidelines, and Expert Recommendations - Ashok Agarwal; Ala’a Farkouh; Ramadan Saleh; Taha Abo-Almagd Abdel-Meguid Hamoda; Gianmaria Salvio; Florence Boitrelle; Ahmed M. Harraz; Ramy Abou Ghayda; Parviz Kavoussi; Murat Gül; Tuncay Toprak; Giorgio Ivan Russo; et al. (The World Journal of Men's Health, 2024)
Purpose: Sperm DNA fragmentation (SDF) is a functional sperm abnormality that can impact reproductive potential, for which four assays have been described in the recently published sixth edition of the WHO laboratory manual for the examination and processing of human semen. The purpose of this study was to examine the global practices related to the use of SDF assays and investigate the barriers and limitations that clinicians face in incorporating these tests into their practice. Materials and Methods: Clinicians managing male infertility were invited to complete an online survey on practices related to SDF diagnostic and treatment approaches. Their responses related to the technical aspects of SDF testing, current professional society guidelines, and the literature were used to generate expert recommendations via the Delphi method. Finally, challenges related to SDF that the clinicians encounter in their daily practice were captured. Results: The survey was completed by 436 reproductive clinicians. Overall, terminal deoxynucleotidyl transferase deoxyuridine triphosphate Nick-End Labeling (TUNEL) is the most commonly used assay chosen by 28.6%, followed by the sperm chromatin structure assay (24.1%), and the sperm chromatin dispersion (19.1%). The choice of the assay was largely influenced by availability (70% of respondents). A threshold of 30% was the most selected cut-off value for elevated SDF by 33.7% of clinicians. Of respondents, 53.6% recommend SDF testing after 3 to 5 days of abstinence. Although 75.3% believe SDF testing can provide an explanation for many unknown causes of infertility, the main limiting factors selected by respondents are a lack of professional society guideline recommendations (62.7%) and an absence of globally accepted references for SDF interpretation (50.3%). Conclusions: This study represents the largest global survey on the technical aspects of SDF testing as well as the barriers encountered by clinicians. Unified global recommendations regarding clinician implementation and standard laboratory interpretation of SDF testing are crucial.